Participatory communication for development: the perspectives of agricultural development agencies in Nigeria - Kigbu, Anna Benson; Ahmad Ghazali, Akmar Hayati; Bidin, Rosmiza; Omar, Siti Zobidah (International Journal of Science and Research (IJSR), 2019)
Background: Participatory communication for development is an important aspect of development projects, as it enhances the participation of the key stakeholders in the development process. As a result of this, so many development agencies are beginning to adopt it in their development projects to enhance participation and project sustainability. However, the use of such communication approach is dependent on the way it is perceived by the development agencies. Therefore, it becomes important to understand how the development agencies perceive participatory communication for development based on their experience in the area of participatory development. To this end, this study was conducted with the aim of exploring the perceptions which agricultural development agencies in Plateau State, Nigeria have of participatory communication for development. A review of the literature shows that in order to understand how this communication approach is used, insight on how it is perceived must be gained first. Methods: This study was conducted using a qualitative case study approach involving two cases in Plateau state, Nigeria. The two cases were purposively selected based on certain criteria. In order to collect data required for the study, a semi-structured in-depth interview was conducted among the study participants, and the data was analysed using qualitative thematic analysis, which allows the researcher to deduct emerging themes that explain the phenomena under study. Findings: Findings of the study revealed that the agricultural development agencies perceive participatory communication for development as a communication approach that enables two way communication and knowledge co-sharing among farmers, and between the farmers and agricultural development agencies.Conclusion: Based on these perceptions, it can be concluded that in the context of agricultural development agencies, participatory communication refers to a twoway communication approach which enables knowledge co-sharing among farmers, and between farmers and the agricultural development agencies.